Molecular characterisation of Staphylococcus aureus and Staphylococcus epidermidis populations from healthy and diseased oral implant and natural tooth sites in a cohort of patients with periimplantitis - Cashin, Phillipa Jane (Trinity College (Dublin, Ireland). School of Dental Science, 2013)
The majority of STs (19/22, 86.36%) belonged to the predominant clonal complex CC1. In comparison to the global S. epidermidis MLST database, the STs identified in this study exhibited no enrichment of or particular association with STs previously identified in healthcare environments, non-human, or environmental isolates, indicating the periimplantitis isolates reflected general carriage isolates.
Keywords: Dental Science, Ph.D.; Ph.D. Trinity College Dublin